Improving the Quality Of Education Through The Application of Students Centered Learning: A Theoretical Review - Novita Anggraeni (Eduvest - Journal of Universal Studies, 2021)
This study aims to describe the application of student-centered learning to improve the quality of education. The results of this study show how the application of student-centered learning has an increase in improving the quality of education, namely: (1) one of factors that can improve the quality of education that must be done is "the children as the center" is excavated so that the school can install the power in the student; (2) the learning process is to built through a continuous question and answer process to improve students' thinking skills so as to obtain knowledge that is constructed by themselves; (3) educational institutions that manage effectively and efficiently will have a positive impact in achieving effective and efficient learning as well, which ultimately results in institutions and develops superior ones. The student-centered learning process can support the expected competencies.